Not so great expectations: The role of price and name information in the nocebo effect - Kiarne Humphreys; Michelle Lin; Kirsten Barnes; Yasmin Hasan; Ashwin Vignaraja; Kritika Sarna; Andrew L. Geers; Kate Faasse (Exploratory Research in Clinical and Social Pharmacy)
Background: The perception of taking a generic medication can result in reduced efficacy and increased side effects, despite equivalence to brand name medications under double blind conditions. It may be that cues typically associated with generics, including lower price and more complex name, exacerbate negative expectations and cause nocebo effects. Methods: Healthy participants (N = 196) were randomised to receive sham-oxytocin nasal spray associated with either a generic (complex name, low price; n = 66) or brand (simple name, high price; n = 68) cue, or to no treatment control (n = 62). Participants were informed that oxytocin could enhance trust and cooperation, but might cause side effects of headache, nausea, vomiting, rapid heartbeat, feeling faint or light-headed, and skin itching or rash. Treatment-related side effects were assessed at baseline, and after 3 days of sham-oxytocin use. Results: Nocebo effects were observed across sham-treated participants relative to control (p = .015; d = 0.28). Association with a generic relative to branded cue significantly enhanced nocebo effects (p = .042; d = 0.36). Negative expectations mediated the observed nocebo and branding effects. Conclusions: Cues associated with generic medications can exacerbate nocebo effects and these findings may explain clinical observations of increased side effects from generic medications. Results have important implications for medical care, and interventions to mitigate nocebo effects from generic medications are needed.